Squamous Metaplasia Is Increased in the Bronchial Epithelium of Smokers with Chronic Obstructive Pulmonary Disease - Rigden, Helen M. (PLoS One, 2016)
AIMS: To quantify the extent of squamous metaplasia in bronchial biopsies and relate it to the presence of chronic obstructive pulmonary disease (COPD), a smoking-related pathology. METHODS: Bronchial biopsies (n = 15 in each group) from smokers with COPD GOLD stage1 and GOLD stage2, smokers without COPD and healthy non-smokers were stained immunohistochemically with a panel of antibodies that facilitated the identification of pseudostratified epithelium and distinction of squamous metaplasia and squamous epithelium from tangentially cut epithelium. The percentage length of each of these epithelial phenotypes was measured as a percent of total epithelial length using computerised image analysis. Sections were also stained for carcinoembryonic antigen and p53, early markers of carcinogenesis, and Ki67, and the percentage epithelial expression measured. RESULTS: The extent of squamous metaplasia was significantly increased in both COPD1 and COPD2 compared to healthy smokers and healthy non-smokers. The amount of fully differentiated squamous epithelium was also increased in COPD1 and COPD2 compared to healthy non-smokers, as was the expression of carcinoembryonic antigen. These features correlated with one other. CONCLUSION: In subjects with COPD there is a loss of pseudostratified epithelium accompanied by an increase in squamous metaplasia with transition into a fully squamous epithelium and expression of early markers of carcinogenesis.